Student Webcam Behaviors and Beliefs: Emergent Norms, Student Performance, and Cultural Differences - Dennen, Vanessa P.; Yalcin, Yasin; Hur, Jaesung; Screws, Bruce (Online Learning, 2022)
This study presents findings from a survey of 2298 university students from three countries (South Korea, Turkey, United States) focused on their use of and beliefs about webcams to support synchronous learning, including behaviors such as turning cameras on and multitasking. Additionally, it explores differences due to national culture, school achievement, and classroom seating preferences. As expected, findings show synchronous learning use increased during the pandemic. Student preferences for passive viewing behaviors are strong, along with preferences for keeping cameras off. Differences based on classroom seating preferences suggest that students who sit at the front are more likely than their peers to make decisions about webcam use based on involvement, attention, and preparedness. Cultural differences suggest different pedagogical expectations. Multitasking proved to be a complex behavior and is not always linked to poor achievement outcomes. This study has implications both for future research directions on synchronous learning, student webcam practices, and achievement and for how instructors design synchronous classes.